2017
DOI: 10.1002/asl.763
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic polar lows and weather regimes: do current links persist in a warmer climate?

Abstract: Polar low development over the North Atlantic under a warmer climate is assessed using simulations of an atmospheric-oceanic coupled general circulation model, specifically with regards to the evolution of large-scale atmospheric variability described by weather regimes, and their links with lower-layer static stability. While a relationship has been identified for the present climate, under a warmer climate, polar low favorable conditions are expected to occur less often, and the large-scale circulation varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Long‐term future changes of CAO occurrence in the Nordic Seas in a warming climate, in contrast, may not primarily be caused by changes of the large‐scale circulation. In fact, climate integrations indicate that the frequency of Euro‐Atlantic WRs in a considerably warmer climate will undergo modest changes only (Mallet et al, ). Hence, long‐term changes in the occurrence of CAOs over the Nordic Seas in a warming climate will most likely be dominated by changes in the availability of cold (with respect to SST) air masses and shifts in CAO formation regions associated with the retreating ice edge (e.g., Fauria et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term future changes of CAO occurrence in the Nordic Seas in a warming climate, in contrast, may not primarily be caused by changes of the large‐scale circulation. In fact, climate integrations indicate that the frequency of Euro‐Atlantic WRs in a considerably warmer climate will undergo modest changes only (Mallet et al, ). Hence, long‐term changes in the occurrence of CAOs over the Nordic Seas in a warming climate will most likely be dominated by changes in the availability of cold (with respect to SST) air masses and shifts in CAO formation regions associated with the retreating ice edge (e.g., Fauria et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Barents Sea however, there are no significant changes. Mallet et al (2017) found that circulation patterns give a reduced influence on the static stability in the future, as sea-ice retreat reduces the variability. The historical link between circulation pattern and static stability (and thus as a proxy for polar lows) is therefore not the same in the future, posing a challenge when using it as part of a statistical downscaling approach.…”
Section: Mcao In Relation To Circulation Patternsmentioning
confidence: 98%
“…Global warming will lead to an increase in the static stability of the atmosphere in the North Atlantic (Zahn and von Storch, 2010;Mallet et al, 2017;Landgren et al, 2019b) and in the North Pacific, although the increase will be smaller in the latter (Landgren et al, 2019b). In the North Atlantic, the SST -T 500 will decrease almost everywhere where PLs develop, and situations of high vertical instability will become less frequent (Mallet et al, 2017). Moreover, the loss of sea ice will lead to a change on the spatial distribution of atmospheric static stability.…”
Section: Impact Of Climate Change On the Climatology Of Plsmentioning
confidence: 99%